Factors affecting smartphone adoption for accessing information in medical settings. (13th April 2017) - Tahamtan, Iman; Pajouhanfar, Sara; Sedghi, Shahram; Azad, Mohsen; Roudbari, Masoud
Abstract: Objectives: This study aimed to acquire knowledge about the factors affecting smartphone adoption for accessing information in medical settings in Iranian Hospitals. Methods: A qualitative and quantitative approach was used to conduct this study. Semi‐structured interviews were conducted with 21 medical residents and interns in 2013 to identify determinant factors for smartphone adoption. Afterwards, nine relationships were hypothesised. We developed a questionnaire to test these hypotheses and to evaluate the importance of each factor. Structural equation modelling was used to analyse the causal relations between model parameters and to accurately identify determinant factors. Results: Eight factors were identified in the qualitative phase of the study, including perceived usefulness, perceived ease of use, training, internal environment, personal experience, social impacts, observability and job related characteristics. Among the studied factors, perceived usefulness, personal experience and job related characteristics were significantly associated with attitude to use a smartphone which accounted for 64% of the variance in attitude. Perceived usefulness had the strongest impact on attitude to use a smartphone. Conclusion: The factors that emerged from interviews were consistent with the Technology Acceptance Model (TAM) and some previous studies. TAM is a reliable model for understanding the factors of smartphone acceptance in medical settings.